2006
DOI: 10.1016/j.virol.2006.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of IL-12 p35 by SJL/J macrophages responding to Theiler's virus infection is associated with constitutive activation of IRF-3

Abstract: Macrophages responding to viral infections may contribute to autoimmune demyelinating diseases (ADD). Macrophages from ADD-susceptible SJL/J mice responding to Theiler's Virus (TMEV) infection, the TLR7 agonist loxoribine, or the TLR4 agonist-LPS expressed less IL-12 p35 but more IL-12/23 p40 and IFN-beta than macrophages from ADD-resistant B10.S mice. While expression of IRF-1 and -7 was similar between B10.S and SJL/J TMEV-infected macrophages, SJL/J but not B10.S macrophages exhibited constitutively active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…6B). Previously, we showed that IRF-3 is constitutively active and localized in the nucleus in SJL/J macrophages (36). Interestingly, in agreement with that finding, we show in this study that IRF-3 is strongly associated with the p19 promoter in unchallenged SJL/J macrophage (Fig.…”
Section: Irf-3 Smad-3 and Atf-2 Are Present At The Endogenous Il-23supporting
confidence: 93%
See 2 more Smart Citations
“…6B). Previously, we showed that IRF-3 is constitutively active and localized in the nucleus in SJL/J macrophages (36). Interestingly, in agreement with that finding, we show in this study that IRF-3 is strongly associated with the p19 promoter in unchallenged SJL/J macrophage (Fig.…”
Section: Irf-3 Smad-3 and Atf-2 Are Present At The Endogenous Il-23supporting
confidence: 93%
“…However, additional phosphorylations through the PI3K/Akt pathway are required for complete activation, binding to the CBP protein, and association with promoter regions (55). We have shown previously that IRF-3 is constitutively active and localized to the nucleus in SJL/J macrophages, which are susceptible to TMEV-induced demyelinating disease, but not in macrophages from B10.S mice, which are resistant to TMEV-induced demyelinating disease (36). ChIP assays presented in this study agree with that observation, in that IRF-3 exhibits strong constitutive association with the endogenous p19 promoter in SJL/J macrophages and to some extent RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Numerous studies have described that elevated IRF-3 activation leads to enhanced antiviral responses, including gross expression of IFNs (53). Therefore, sustained phosphorylation may imply an expected elevation of cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, sustained phosphorylation may imply an expected elevation of cytokine production. More recently, however, experiments in macrophages (54) have detailed reduced expression of IL-12 p35 in response to viral infection due to constitutive activation of IRF-3 and its function as a repressor of transcription via binding to bp 2172 to 2122 of the p35 promoter (53). Whether this regulatory function is apparent in BMDCs and can be correlated with IRF-3 protein phosphorylation status remains to be determined.…”
Section: Discussionmentioning
confidence: 99%